Literature and the "good doctor" in Ian McEwan's Saturday. Issue 2 (30th November 2007) - Macnaughton, J
Abstract : There is widespread acceptance in medical humanities circles that reading is good for doctors and that, in medical educational terms, it is particularly good at making better doctors by widening perspective and developing the sensibilities. Recent recommendations on medical education in the UK have allowed medical students to take courses in literature as a component of their degrees, and some have suggested that this option should be compulsory for all doctors. It is possible, however, that in our eagerness to assert the primacy of a literary education for personal development, we can ignore other routes to enlightened, sensitive doctoring. This paper appraises the instrumental role of a literary education for doctors through an analysis of Ian McEwan's novel Saturday, which deals with the dramatic events in the day in the life of a neurosurgeon.